Analysis of the Differences in the Quality of Life of Pulmonary TB and Diabetes Mellitus Patients - Hadi, Zulfi Wirman; Sastrawan, Sastrawan; Sismulyanto, Sismulyanto (Journal La Medihealtico, 2025)
The low quality of life of pulmonary TB sufferers is in physical, psychological and social aspects, while diabetes mellitus sufferers show a better quality of life. Social stigma, limited social support, and stress due to complex illnesses and treatments are also problems that affect patients' mental and emotional conditions. This study used a comparative design to compare the quality of life of individuals with TB and DM at the Meninting Community Health Center UPT. Data collection in July 2024 with a cross-sectional design. The findings of this research are that there is a significant difference in the quality of life between pulmonary TB and diabetes mellitus (DM) sufferers in the Meninting Community Health Center UPT Working Area, West Lombok Regency. DM sufferers tend to have a better quality of life in physical, psychological, social and environmental health indicators compared to pulmonary TB sufferers. This can be caused by factors such as social support, physical abilities, and living environment. This study shows the need for more intensive attention to pulmonary TB sufferers in improving the quality of life, especially in social and environmental aspects, in order to improve welfare conditions.